Gas sorption and transport in polyarylates: effect of substituent symmetry and polarity - Karadkar, Prasad B.; Kharul, Ulhas K.; Bhole, Yogesh S.; Badhe, Yogesh P.; Tambe, Sanjeev S.; Kulkarni, Bhaskar D. (Journal of Membrane Science, 2007)
The gas sorption properties of polyarylates based on bisphenol-A possessing symmetric/asymmetric substitution by nonpolar -CH3 group and symmetrically linked terephthalic acid were examined. The effects of substitution of polar bromine on terephalic acid moiety of polyarylate based on asymmetrically substituted bisphenol were also studied for physical, sorption and transport properties. The estimation of dual mode sorption parameters, solubility and diffusion coefficient revealed that nature of the substituent and substitution type plays a crucial role in depicting permeation properties. An asymmetric substitution by -CH3 group increased solubility coefficient of pure gases (N-2, O-2, CH4 and CO2) up to 27% and symmetric substitution increased the same up to 106%. This was coupled with 7-35% increase in solubility selectivity in both cases of substitution, which ascertained the usefulness of methyl group substitution in polyarylates based on terephalic acid. The pressure dependency of solubility coefficients and solubility selectivity was also investigated for these polyarylates. The sorption and transport properties of these polyarylates correlated well with physical properties of polyarylates and gases studied. The sorption/desorption kinetics of symmetrically substituted TMBisA-T was performed in order to deduce time dependent sorption behavior and to evaluate diffusivity coefficient. The apparent diffusion coefficients from sorption kinetics, desorption kinetics and from steady-states permeation-sorption were compared. The diffusion coefficients of CH4 and N-2 deduced by these methods correlated well with each other. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Diffusion; kinetics; permeation; polyarylates; Sorption

Green synthesis of silver nanoparticles using sunlight - Bhaduri, Gaurav A.; Little, Ross; Khomane, Ramdas B.; Lokhande, Suhas U.; Kulkarni, Bhaskar D.; Mendis, Budhika G.; Siller, Lidija (Journal of Photochemistry and Photobiology A-Chemistry, 2013)
Silver nanoparticles (AgNPs) are currently among the most widely used man-made nanomaterials, present in a huge range of consumer products. Here we report a simple `green' method of AgNP synthesis of using an anionic surfactant without use of any additional reducing agents. It was observed that synthesis of AgNPs at room temperature (25-35 degrees C) using sodium dodecyl sulphate (SDS) and sunlight. The nanoparticles have been characterised using high-resolution transmission electron spectroscopy (HRTEM), UV-vis spectrophotometry, X-ray photoelectron spectroscopy (XPS) and Fourier Transform Infrared Spectroscopy (FTIR) and are found to have an average diameter of 30 nm. The nanoparticles are water soluble and the nature of the process is amenable to scaling up. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: photochemistry; silver nanoparticles; Sodium dodecyl sulphate; XPS